Analysis of Osing Cultural Literacy among Junior High School Students in Banyuwangi Regency: Cognitive, Affective, and Behavioral Dimensions - Siti Cholifah Amaliyah; Wisnu Wisnu; M. Jacky (Sakura Digital Nusantara, 2026)
Purpose: This study aimed to analyze the cognitive, affective, and behavioral dimensions of Osing cultural literacy among junior high school students in Banyuwangi Regency and to examine differences in cultural literacy levels among schools. Method: This study employed a quantitative descriptive design involving 200 seventh-grade students from four junior high schools in Banyuwangi Regency, namely SMP Negeri 1 Glagah, SMP Negeri 2 Glagah, SMP Negeri 1 Giri, and SMP Negeri 1 Licin, selected through proportional random sampling. Data were collected using an Osing cultural literacy questionnaire consisting of cognitive, affective, and behavioral indicators measured using a Likert scale. Data were analyzed using descriptive statistics and the Kruskal–Wallis test after normality and homogeneity testing. Results: The results showed that students’ Osing cultural literacy levels were generally categorized as high to very high across all schools. In the cognitive dimension, the mean scores were 14.18 at SMP Negeri 1 Glagah, 14.18 at SMP Negeri 2 Glagah, 14.56 at SMP Negeri 1 Giri, and 14.16 at SMP Negeri 1 Licin, all categorized as very high. In the affective dimension, the mean scores ranged from 35.18 to 36.32 and were also categorized as very high. Meanwhile, the behavioral dimension obtained relatively lower mean scores ranging from 27.82 to 32.34, although still categorized as high. The Kruskal–Wallis test indicated no significant differences in Osing cultural literacy levels among schools (p > 0.05), suggesting relatively homogeneous cultural literacy among students. Research Implications: These findings highlight the important role of schools in strengthening local cultural literacy through the integration of Osing cultural values into learning activities and school programs. Originality: This study contributes empirical evidence regarding the multidimensional measurement of Osing cultural literacy among junior high school students in Banyuwangi Regency.